2012
DOI: 10.1017/s1041610212000683
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomized controlled trial of humor therapy in residential care: the Sydney Multisite Intervention of LaughterBosses and ElderClowns (SMILE)

Abstract: SMILE is the first large rigorous study of humor therapy in aged care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…The Study protocol details have been reported previously 16. Ethics approval was obtained from the University of New South Wales Human Research Ethics Committee (approval number 08345).…”
Section: Methodsmentioning
confidence: 99%
“…The Study protocol details have been reported previously 16. Ethics approval was obtained from the University of New South Wales Human Research Ethics Committee (approval number 08345).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the health sector, humor interventions have also been investigated in the field of positive psychology (Ruch and McGhee, 2014 ; Ruch and Hofmann, 2017 ). Some studies in medical settings were conducted with older people in nursing homes (Mathieu, 2008 ; Goodenough et al, 2012 ; Low et al, 2013 ), cancer patients (Itami, 2000 ; Venter et al, 2008 ), veterans (Steinhauser et al, 2000 ), and patients suffering from depression (Shahidi et al, 2011 ). Positive correlations have been reported on humor and laughter in relation to life satisfaction outside the health care setting (Wild et al, 2003 ; Ruch et al, 2010 ), and there is some evidence of a relationship between humor and health (Martin, 2001 , 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The same can be said about studies investigating the influence of humor on geriatric patients with mental diseases. Recently, Nauert (2011) referenced an as yet unpublished result by a research group (for study protocol, see Goodenough et al, 2012) reportedly showing a 20% decrease in agitation in patients with dementia. Happiness and positive behaviors rose but only for the duration of the program.…”
Section: Introductionmentioning
confidence: 99%